Application of 3D printing in the treatment of diabetic foot ulcers: current status and new insights - Li, Xinrui; Ai, Xin; Wang, Bo; Luo, Mengqian; Miyamoto, Akira; Kuchay, Mohammad Shafi; Feng, Dechao; Zhang, Chi (Frontiers in Bioengineering and Biotechnology, 2024)
Background and Aims Diabetic foot ulcers (DFUs) are a serious complication of diabetes mellitus (DM), affecting around 25% of individuals with DM. Primary treatment of a DFU involves wound off-loading, surgical debridement, dressings to provide a moist wound environment, vascular assessment, and appropriate antibiotics through a multidisciplinary approach. Three-dimensional (3D) printing technology is considered an innovative tool for the management of DFUs. The utilization of 3D printing technology in the treatment of DFU involves the modernization of traditional methods and the exploration of new techniques. This review discusses recent advancements in 3D printing technology for the application of DFU care, and the development of personalized interventions for the treatment of DFUs. Methods We searched the electronic database for the years 2019–2024. Studies related to the use of 3D printing technology in Diabetic foot were included. Results A total of 25 identified articles based on database search and citation network analysis. After removing duplicates, 18 articles remained, and three articles that did not meet the inclusion criteria were removed after reading the title/abstract. A total of 97 relevant articles were included during the reading of references. In total, 112 articles were included. Conclusion 3D printing technology offers unparalleled advantages, particularly in the realm of personalized treatment. The amalgamation of traditional treatment methods with 3D printing has yielded favorable outcomes in decelerating the progression of DFUs and facilitating wound healing. However, there is a limited body of research regarding the utilization of 3D printing technology in the domain of DFUs.